2020
DOI: 10.21203/rs.3.rs-15608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between parental separation and addictions in adolescents: results of a national Lebanese study

Abstract: Objectives: to investigate the association between the divorce of parents and smoking, alcohol, and internet addiction among a representative sample of Lebanese adolescents.Methods: This study was a cross-sectional, conducted between January and May 2019 using a proportionate random sample of schools from all Lebanese Mohafazat. Out of 2000 questionnaires distributed; 1810 (90.5%) were completed and collected back.Results: The mean age was 15.42 ± 1.14 years, with 53.3% females and 74.1% smokers. In addition, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Based on the Problem Behavior Theory and Bowlby’s early attachment theory, several studies have shown that adolescents who experience insecure attachment secondary to the separation from a parent, might exhibit social, psychological, or behavioral disruption [ 3 6 ]. This increase in risk behaviors, includes but is not limited, to cigarette and waterpipe addiction [ 3 , 4 , 7 ]. In fact, Lebanese, European and American studies have reported higher rates of nicotine addiction in adolescents who have experienced parental divorce at an early age, when compared to those who lived with both parents [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the Problem Behavior Theory and Bowlby’s early attachment theory, several studies have shown that adolescents who experience insecure attachment secondary to the separation from a parent, might exhibit social, psychological, or behavioral disruption [ 3 6 ]. This increase in risk behaviors, includes but is not limited, to cigarette and waterpipe addiction [ 3 , 4 , 7 ]. In fact, Lebanese, European and American studies have reported higher rates of nicotine addiction in adolescents who have experienced parental divorce at an early age, when compared to those who lived with both parents [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in risk behaviors, includes but is not limited, to cigarette and waterpipe addiction [ 3 , 4 , 7 ]. In fact, Lebanese, European and American studies have reported higher rates of nicotine addiction in adolescents who have experienced parental divorce at an early age, when compared to those who lived with both parents [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showed that individuals with anxiety reported more waterpipe attachment than individuals with no anxiety. A study done in Lebanon showed that adolescents with divorced parents, 58 insecure attachment style, that have low self‐esteem and more anxiety, 59 are prone to waterpipe addiction more than the others. This can be explained by two points.…”
Section: Discussionmentioning
confidence: 99%